2021
DOI: 10.1002/oby.23263
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus increases the risk of hepatic fibrosis in individuals with obesity and nonalcoholic fatty liver disease

Abstract: Objective This study assessed the impact of diabetes mellitus (DM) on nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) with advanced fibrosis prevalence in adults with overweight or obesity in the United States. Methods Participants (National Health and Nutrition Examination Survey [NHANES] 2015‐2016 database) included 834 middle‐aged patients with DM (21.7%) and 3,007 without DM (78.3%). NAFLD was defined by Fatty Liver Index (FLI) ≥ 60 or United States FLI (USFLI) ≥ 30. Modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 46 publications
7
57
0
1
Order By: Relevance
“…The FLI had an AUC of 0.84, and the USFLI had an AUC of 0.80 to detect steatosis in the U.S. population [ 14 ]. We used a combination of these two indexes as previously described [ 44 ]. We performed a sensitivity analysis to test these patients and found that the association between RBC folate and NAFLD was stable whether FLI or USFLI was used ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FLI had an AUC of 0.84, and the USFLI had an AUC of 0.80 to detect steatosis in the U.S. population [ 14 ]. We used a combination of these two indexes as previously described [ 44 ]. We performed a sensitivity analysis to test these patients and found that the association between RBC folate and NAFLD was stable whether FLI or USFLI was used ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients screened in primary care will have a low risk of clinically significant liver fibrosis, defined as having a FIB-4 score <1.3, LSM <8.0 kPa by transient elastography, or a liver biopsy fibrosis stage of F0-F1 (Figure 3). 1,2,[50][51][52][53] We recommend therapeutic lifestyle interventions for these patients. Specific pharmacologic treatment targeting liver steatosis is not necessary in this lower-risk population.…”
Section: Management Of Nonalcoholic Fatty Liver Disease In Patients At Low Risk Of Advanced Fibrosismentioning
confidence: 99%
“…Nearly 10% of patients screened based on Steps 1 to 4 will have a high risk of clinically significant liver fibrosis, defined as having a FIB-4 score >2.67, LSM >12.0 kPa by transient elastography, or a liver biopsy showing clinically significant liver fibrosis (Figure 3). 1,2,[50][51][52][53] We recommend that these patients be managed by a multidisciplinary team closely coordinated by a hepatologist who can monitor for cirrhosis, HCC, and other cirrhosis-related complications. In these patients, we recommend aggressive lifestyle changes aimed at long-term weight loss.…”
Section: Management Of Nonalcoholic Fatty Liver Disease In Patients At High Risk Of Advanced Fibrosismentioning
confidence: 99%
“…TO THE EDITOR: We read with great interest the recently published Obesity article in which Barb et al (1) observed that prevalence of nonalcoholic fatty liver disease (NAFLD) in US participants was primarily driven by obesity and that people with diabetes had greater risk of NAFLD and advanced fibrosis. Indeed, 31.0% of those with obesity and diabetes had a fibrosis-4 index score indicating moderate-to-high risk, and 34.1% had an NAFLD fibrosis score (NFS) suggesting high risk of advanced fibrosis.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%